Towards digital solutions for VPC germplasm management in Africa - Gatimu, R.; Ogero, K. (2025)
This technical brief outlines the process of developing digital systems for managing germplasm of vegetatively propagated crops (VPCs) — including sweetpotato, potato, banana, yam, and cassava — across Kenya, Uganda, and Tanzania. Led by CIP in collaboration with IITA and KEPHIS, the initiative developed a blueprint for sustainable digital transformation and informed the creation of the Roots, Tubers and Banana East Africa Germplasm Exchange Laboratory (RTB-EAGEL) digital system. Crop-specific digital workflows were established, along with a Business Investment Decision (BID) tool and Operational Business Plan to ensure system sustainability. Lessons highlight the need for user-centered design, local technical capacity, affordable maintenance, and integration into real operational workflows for successful digitalization in African seed systems.